A critical chain perspective to support management activities in dynamic production networks - Tenera, Alexandra (2008)
Collaborative networks are typically assumed to bring clear benefits and competitive advantage to the participating members. However, as the networks are typically formed by heterogeneous and autonomous enterprises, the development of methodologies that facilitates the management process is an important element for the wide adoption of this paradigm. Departing from a brief presentation of the Critical Chain Project Management approach, the paper introduces this approach to collaborative networks and discusses its potential application in the context of a dynamic production networks. Finally, experimental results based on data from a network in construction industry are presented.